PENGARUH PELAKSANAAN PROGRAM KELAS IBU HAMIL TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL DALAM DETEKSI DINI RESIKO TINGGI - Tinah - (Universitas Muhammadiyah Semarang, 2014)
The expectation of class for pregnant women are interaction and sharing of experiences amongparticipants or pregnant women with a midwife or health workers about pregnancy, bodychanges, complaints during pregnancy, prenatal care, intranatal care, postnatal care, infant care,local myths or beliefs, infectious diseases, and a birth certificate.The objectives of this research is to analize the influence of pregnant women’s classimplementation toward knowledge and attitude pregnant women into high-risk early detection.Method of this research using comparative studies with prospective research type andquantitative approach. This research population is the entire third trimester pregnant womenwho live in villages that have program of class for pregnant women in the area of Teras healthcenters Boyolali, with total sample of 38 person, using total sampling method. Data obtained,such as the frequency of pregnant women’s presence into class, knowledge and attitude ofpregnant women toward early detection of high-risk pregnant women. Data were analyzed usingstatistical test, t-test. The result showing that there is an influence between implementation ofclass for pregnant women toward knowledge of pregnant women into high-risk early detection(tcalculation < t , 81.494 > 2,021) and probability value is lower than level of significant 5% Sig.(2-tailed) > 0,05 (0,000<0,05), there is an influence between implementation of class forpregnant women toward attitude of pregnant women into high-risk early detection (ttable <t , 42.349 > 2,021) and probability value is lower than level of significant 5% Sig. (2-tailed)> 0,05 (0,000<0,05). Thus, needs to be continued and enhanced motivation of pregnant women,families, and health workers especially midwives, in implementation of class for pregnantwomen.Keywords: Implementation of class for pregnant women, Knowledge, Attitude, High-Risk Early tablecalculation